POS0747 CORRELATIONS BETWEEN CAPILLARY DENSITY AND DEGREE OF SKIN PIGMENTATION IN HEALTHY CHILDREN ANALYSED BY NAILFOLD VIDEO CAPILLAROSCOPY - Bergkamp, S.; Smith, V.; Kuijpers, T.; Cutolo, M.; Van den Berg, J. M.; Schonenberg-Meinema, D. (Annals of the rheumatic diseases, 2023)
BackgroundNailfold Video Capillaroscopy (NVC) is a simple, non-invasive diagnostic tool but studies with normal values for capillary density in healthy children are rare. Ethnic background seems to play a role in capillary density; however, this is not well substantiated yet [1,2].ObjectivesIn this work, we set out to evaluate influence of ethnic background/skin pigmentation and age on capillary density reading in healthy children. Secondary aim was to investigate whether there is a significant difference in density between different fingers within the same patient.MethodsCapillaroscopic images from healthy children were obtained in a one-time visit videocapillaroscopy (x200 magnification) addressing the capillary density (i.e. number of capillaries per linear millimeter in the distal row). This parameter was compared to age, sex, ethnicity, skin pigment grade (I-III) and between eight different fingers, excluding the thumbs.ResultsWe investigated 145 healthy children with mean age of 11.03 years (SD 3.51). The range of capillary density was 4-11 capillaries per millimetre. We observed a lower capillary density in the ‘grade II’ (6.4 ± 0.5cap/mm, p<0.001) and ‘grade III’ (5.9 ± 0.8 cap/mm, p<0.0001) pigmented-classified groups compared to the ‘grade I’ group (7.0 ± 0.7 cap/mm). We did not find a significant correlation between age and density in the overall group. The fifth fingers on both sides had a significantly lower density compared to the other fingers.ConclusionHealthy children <18 years with higher degree of skin pigmentation show a significantly lower nailfold capillary density. In subjects with an African/Afro-Caribbean and North-African/Middle-Eastern ethnicity, a significantly lower mean capillary density was observed compared to subjects with the Caucasian ethnicity (p<0.0001, and p<0.05, respectively. There were no significant differences between other ethnicities. No correlation was found between age and capillary density. The fifth fingers on both hands displayed lower capillary density compared to the other fingers. This needs to be taken into account when describing lower density in paediatric patients with connective tissue diseases.References[1]Andrade LE, Gabriel Júnior A, Assad RL, Ferrari AJ, Atra E. Panoramic nailfold capillaroscopy: a new reading method and normal range. Semin Arthritis Rheum. 1990;20(1):21-31.[2]Karbalaie A, Emrani Z, Fatemi A, Etehadtavakol M, Erlandsson BE. Practical issues in assessing nailfold capillaroscopic images: a summary. Clin Rheumatol. 2019.AcknowledgementsWe would like to thank all healthy children, their parents and the schools “Piet Hein”, “de Knotwilg” and “Burgemeester Amersfoordtschool” for participating in our study, by undergoing a one-time capillaroscopy.Disclosure of InterestsNone Declared.